Extreme Premature Small for Gestational Age Infants Have Appropriate Catch-up Growth at Term Equivalence Compared with Extreme Premature Appropriate for Gestational Age Infants - Sze May Ng; Donatella Pintus; Mark A. Turner (Galenos Yayincilik, 2019)
Recent studies have shown that small for gestational age (SGA) term infants undergo catch-up growth during infancy but there is limited studies on early growth outcomes of extreme premature SGA infants. The aim of this study was to compare factors associated during birth in extremely premature infants less than 28 weeks' gestation who were born SGA (<10th percentile for gestational age) with those who were born appropriate-for-gestational age (AGA) (10th-89th percentile) and to determine whether there was catch-up growth at term equivalence. One hundred fifty-three extreme premature infants (89 males) born below 28 weeks' gestation were prospectively recruited. All infants had auxological measurements undertaken and prospective data on pregnancy, maternal factors, perinatal and postnatal data obtained. SGA infants at birth had significantly higher Clinical Risk Index for Babies scores and mortality, lower birth weight, smaller head circumference, smaller mid arm circumference and shorter leg length at time of birth compared with AGA infants. However, at term equivalence, weight and leg length of were not significant between AGA and SGA infants born at extreme prematurity. Our study shows that extreme premature SGA infants have appropriate catch-up growth by the time they reach term equivalence suggesting that postnatal nutrition and care are important determinants of catch-up growth in SGA infants.